2007
DOI: 10.1186/1746-4269-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicinal plant knowledge and use by local healers in Sekoru District, Jimma Zone, Southwestern Ethiopia

Abstract: The knowledge and use of medicinal plant species by traditional healers was investigated in Sekoru District, Jimma Zone, Southwestern Ethiopia from December 2005 to November 2006. Traditional healers of the study area were selected randomly and interviewed with the help of translators to gather information on the knowledge and use of medicinal plants used as a remedy for human ailments in the study area. In the current study, it was reported that 27 plant species belonging to 27 genera and 18 families were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
152
6
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(225 citation statements)
references
References 27 publications
65
152
6
2
Order By: Relevance
“…Medicinal plant source habitats in the study area are consistent with the findings of Yineger and Yewhalaw (2007) where most of the medicinal plants (85.7%) utilized in southwestern Ethiopia were harvested from the wild. Of the cultivated plants, only W. somnifera and A. vera were cultivated primarily for their medicinal values.…”
Section: Habitat Growth Forms and Plant Parts Used Habitatsupporting
confidence: 77%
See 2 more Smart Citations
“…Medicinal plant source habitats in the study area are consistent with the findings of Yineger and Yewhalaw (2007) where most of the medicinal plants (85.7%) utilized in southwestern Ethiopia were harvested from the wild. Of the cultivated plants, only W. somnifera and A. vera were cultivated primarily for their medicinal values.…”
Section: Habitat Growth Forms and Plant Parts Used Habitatsupporting
confidence: 77%
“…Gidey et al (2009) also a significantly higher number of medicinal plants are reported by informants above 40 years of age among the Bench ethnic group. However, Yineger and Yewhalaw (2007) reported a statistically insignificant correlation between age and the number of medicinal plants by the local people in Jimma zone, south western Ethiopia. This could be related to knowledge acquisition by the lower age class in that locality.…”
Section: Knowledge Distribution Of Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the preferred source of medicinal plants varies from region to region, even from country to country, depending on availability. Unlike respondents in the study area, the Shaiji of Bangladesh (Halim et al 2007), traditional healers of Ethiopia (Yineger and Yewhalaw 2007) and local people in China (Lee et al 2008) generally prefer wild-harvested medicinal plants. Halim et al (2007), citing Palevitch (1991) and Uniyal et al (2000), with regard to preferences of communities for collecting medicinal plant parts from wild sources, noted that the medicinal properties of plant secondary metabolites produced under stress and competition are not always expressed in fast-growing monoculture.…”
Section: Sources Of Medicinal Plantsmentioning
confidence: 99%
“…Honey was also commonly added to preparations with the view of enhancing palatability and thereby improving compliance towards therapy. A study carried out by Yineger et al (2007) found that in most of remedy preparations, sugar, honey, tea, coffee, edible oil and garlic were the additives that were used. In the present study, various parts of plants were found to be utilised for the herbal formulations, with leaves being the most commonly used plant parts.…”
Section: Discussionmentioning
confidence: 99%